The Navigability Validation for Middle East E-governments Websites - Al-Alem, Fatima (Journal of engineering sciences and information technology, 2017)
The current study aimed to guarantee websites quality, we should evaluate them depending on certain criteria, this is to achieve the best service. This work aimed to build a platform to evaluate the navigability validation for some e-government websites. As a contribution to the field of websites evaluation, this study evaluates the quality of e-government portal website for 15 countries in the Middle East by using common automatic website evaluation tools. The proposed websites evaluation approach is conducted according to certain metrics based on five automatic website tools which are: Link checker, Xenu, page rank, Alexa, and TAW, those tools are freely available for evaluation purposes.  The assessment of these websites helps their developers for improving them and following the quality principles. We tested accessibility, usability and page rank as three criteria of websites quality assessment. Our findings may improve some standards when building and developing Middle East E-government websites, finally, they presented some recommendations to avoid the weak points in these websites.